THE USE OF TRAFFIC SIGN PICTURES TO IMPROVE THE STUDENTS’ ABILITY IN CONSTRUCTING IMPERATIVE SENTENCE - Nurhalijah Nurhalijah; Ismail Latief (Inspiring: English Education Journal, 2019)
One of grammatical pattern of English that is important to be taught is imperative sentences. By having the knowledge about imperative sentences, students are supposed to be able to construct the sentences correctly. Although the students have learnt imperative sentences at school, most of them still find difficulties in understanding and using them. This study aimed at finding out whether using of traffic sign pictures able to improve the students’ ability in constructing imperative sentence. This study was conducted at the seventh grade of SMPN 2 Tellu Limpoe kabupaten Sidenreng Rappang by using pre-experimental method with one group on pre-test and post-test design. This study was conducted in eight meeting which consist of one meeting for pre-test, six meeting for treatment, and one meeting for post-test. The data were gathered through quantitative data. The study found out the use of traffic sign pictures was able to improve the students’ ability in constructing imperative sentence. This study also provides a set of recommendation to avoid the overlapped researches in English education.